Forestry feedbacks in Malezales’ degradation: Insights from past to plan future policy-driven forestry expansion over wetlands in Argentina - Pereira, Luís Flávio; Kurtz, Ditmar Bernardo; Fernandes Filho, Elpídio Inácio (Elsevier, 2023)
The degradation of wetlands is a worrying phenomenon, given its ecosystemic importance due to the provision of environmental services. In Argentina, the process of wetland degradation is fast and almost unknown due to the lack of control and monitoring. Malezales grasslands are wetland ecosystems, indeed poorly studied and endemic of Argentina's northeast. This study aimed to understand the impacts of policy-driven forestry expansion in wetlands, searching for tools and patterns to plan sustainable afforestation. Geographic information systems and remote sensing-based models were used to produce and analyze historical data of the forestry expansion and malezales degradation on inceptsols located in northeastern Corrientes, Argentina. The results showed that the region experienced extensive forestry expansion over the last 20 years. Pinus spp. plantations expanded on the most degraded malezales, which suggests some sustainability in the expansion process. However, the remaining malezales present current worrying levels of degradation. The intensification of the degradation process is imminent because livestock pressure on malezales has been intensified after the loss of areas due to the forestry increasing. We present a preliminary zoning of areas for conservation or forestry expansion in malezales. We found that 40.2% (47571 ha) of the current area of malezales could be used for forestry expansion, while 59.81% (about 70793 ha, 41.56% of the original ecosystem) is of priority for conservation or protection actions. A complete zoning of malezales is recommended, and policies to foment the correct management of malezales and forestry should therefore be implemented.